Pelatihan Pembuatan Pupuk Organik Padat dari Limbah Pertanian di Kelompok Tani Sadar Kelurahan Limbukan guna Mendukung Pertanian Berkelanjutan - Deliana Andam Sari; Rinda Yanti; Hasan Ibrahim; Setya Dharma (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Waste from agricultural products such as straw, husks, leaves and grass which are easily available, are recycled and broken down with the help of decomposer microorganisms such as bacteria and fungi. The methods used in community service activities are the diffusion of science and technology and training to the Sadar farmer group regarding making solid organic fertilizer, demonstrations/training. Service activities were carried out from April 2024 to September 2024. From the results of the service that was carried out, farmers were very enthusiastic about adopting the technology that was provided during the activity. Farmers directly apply the resulting solid organic fertilizer products to corn plants. The use of solid organic fertilizer is applied to the planting land 1 week before planting.